2021
DOI: 10.18632/aging.202873
|View full text |Cite
|
Sign up to set email alerts
|

Anti-aging effects of a functional food via the action of gut microbiota and metabolites in aging mice

Abstract: Wushen (WS) is a mixed food containing 55 natural products that is beneficial to human health. This study aimed to reveal the preventive effect of WS on aging via a combined analysis of gut microbiome and metabolome. Senescence-accelerated mouse prone 8 (SAMP8) mice were used as aging model and senescence-accelerated mouse resistant 1 (SAMR1) mice as control. The mice were fed four diet types; control diet (for SAMR1 mice), standard diet (for SAMP8 mice, as SD group), WS diet, and fecal microbiota transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Gut microbiota-targeted interventions have been conducted to retard aging and improve host health ( 20 ). A preventive effect of natural functional food on aging via the regulation of gut microbiota and relevant metabolites has also been demonstrated ( 21 ). Gut microbiota transplantation of young donors is evident to reverse age-associated impairments in the peripheral and brain immunity, and cognitive behavior in older recipients ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota-targeted interventions have been conducted to retard aging and improve host health ( 20 ). A preventive effect of natural functional food on aging via the regulation of gut microbiota and relevant metabolites has also been demonstrated ( 21 ). Gut microbiota transplantation of young donors is evident to reverse age-associated impairments in the peripheral and brain immunity, and cognitive behavior in older recipients ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the functional food Wushen (WS), which is a powdered mixture of 55 foods, interferes with the body’s gut microbiota through a complex composition of compounds in the food to exert anti-aging effects. After feeding WS to SAMP8 mice, the intestinal microbiota of the WS group displayed a marked enhancement in the abundance of Luminococcus and Butyrivella and a reduction in Clostridium pullulans , Clostridium luminous , Bacteroides coelicolor, and Investinimonas , with changes in the metabolic profile, especially for metabolites involved in linoleic acid metabolism and neuroactive ligand–receptor interactions ( Zhang et al, 2021 ). In comparison with the controls, WS effectively alleviated aging-related decreases in food intake, body weight, muscle mass, and adiposity, improved learning and memory abilities, attenuated cognitive decline, and enhanced immune function in mice ( Zhang et al, 2021 ).…”
Section: Delaying Aging Through the Gut Microbiotamentioning
confidence: 99%
“…Aging, a complex progressive process, encompasses a network of mechanisms, including central and peripheral inflammation, oxidative stress, and immune‐senescence, leading to aging‐related diseases [1–3]. By 2030, around 20% of the world population will be over 65 [4–7]. Data showed that the risk of renal diseases will increase in older people (≥65 years), and aging may enhance the severity of acute kidney injury in this population.…”
Section: Introductionmentioning
confidence: 99%